A NOTE ON THE DISTRIBUTION AND HABITAT PREFERENCE OF Cyclotus longipilus VON MARTENS, 1865 FROM THE MAROS KARST AREA OF SOUTH SULAWESI (GASTROPODA: CYCLOPHORIDAE) - Ristiyanti M. Marwoto (BRIN Publishing (Penerbit BRIN), 2007)
-